(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The term "bronchial asthma" is commonly understood as a chronic recurrent inflammatory process in the respiratory tract, mainly of allergic origin, which leads to their hyperreactivity, labile obstruction and the appearance of respiratory symptoms such as paroxysms, dyspnea or attacks of expiratory suffocation, up to asthmatic status, wheezing and cough. This disease has been known to mankind since the 3rd-2nd centuries BC from the works of the most ancient doctors - Hippocrates and Aretaeus. To this day, hundreds of scientific papers have been published around the world devoted to various aspects of bronchial asthma, but nevertheless, the problems of etiopathogenesis and treatment of this disease have not yet found their solution. Moreover, due to environmental pollution and chemicalization of agriculture, production and everyday life, allergization of the population has increased everywhere , which is manifested by the incidence of bronchial asthma. Thus, according to epidemiological studies, 1-18% of the world’s population suffers from bronchial asthma of varying severity. According to WHO, the number of people with bronchial asthma in some countries is 3-7 times higher than cancer patients and 25-100 times higher than tuberculosis patients. Every year, at least 80 thousand people die from bronchial asthma worldwide. More than 50% of healthcare costs for the treatment of elderly patients with bronchial asthma are spent on purchasing medications. The economic damage from this disease also reaches billions of dollars per year, which confirms the relevance of the problem.